PHF2 regulates homology-directed DNA repair by controlling the resection of DNA double strand breaks - Alonso-de Vega, Ignacio (Nucleic Acids Res, 2020)
Post-translational histone modifications and chromatin remodelling play a critical role controlling the integrity of the genome. Here, we identify histone lysine demethylase PHF2 as a novel regulator of the DNA damage response by regulating DNA damage-induced focus formation of 53BP1 and BRCA1, critical factors in the pathway choice for DNA double strand break repair. PHF2 knockdown leads to impaired BRCA1 focus formation and delays the resolution of 53BP1 foci. Moreover, irradiation-induced RPA phosphorylation and focus formation, as well as localization of CtIP, required for DNA end resection, to sites of DNA lesions are affected by depletion of PHF2. These results are indicative of a defective resection of double strand breaks and thereby an impaired homologous recombination upon PHF2 depletion. In accordance with these data, Rad51 focus formation and homology-directed double strand break repair is inhibited in cells depleted for PHF2. Importantly, we demonstrate that PHF2 knockdown decreases CtIP and BRCA1 protein and mRNA levels, an effect that is dependent on the demethylase activity of PHF2. Furthermore, PHF2-depleted cells display genome instability and are mildly sensitive to the inhibition of PARP. Together these results demonstrate that PHF2 promotes DNA repair by homologous recombination by controlling CtIP-dependent resection of double strand breaks.